Strengthening Municipalities’ Resilience against Cyber Attacks in Ukraine .......... 171 - Fyshchuk, Iryna (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
A full-scale war was preceded by cyberattacks on the websites of public authorities in Ukraine in the spring of 2022. Joint efforts between IT professionals from the public and private sectors have produced positive experience and resilience in resisting cyberattacks. Ukraine’s ongoing decentralization process created new administrative-territorial system, where municipalities acquired more functions and responsibilities. This transformational period involves a weaker governance structure that is highly vulnerable to cyberattacks. Strengthening municipalities’ resilience in Ukraine during the ongoing war refers to the ability of a community to manage itself with cyberattack challenges and to overcome change and crisis. The resilience of a municipality should be to understand, and capacity to respond against cyberattacks and describe institutional structures should be developed at the local level. Leadership is one of the key elements of municipal resilience at the local level. Furthermore, Ukraine’s accession to the Digital Europe 2027 Programme could potentially provide municipalities with better funding for cybersecurity implementation and move closer to EU standards. The Digital Europe Programme is available through other EU programs, such as Connecting Europe Facility for digital infrastructure and the Recovery and Resilience Facility, to which Ukrainian municipalities will be able to apply.